Seetan : Sistem Pengendalian Sosial Masyarakat Desa Pakraman Susut Kelod, Bangli - Hadiputra Evaganna, Made Andika; Sukardja, Putu; Darmana, Ketut (Humanis; Vol 20 No 1 (2017), 2017)
Social control is needed to overcome the deviant behavior of an individual or group in society. Susut Kelod village has uniqueness to overcome the problem with seetan as a tool of absenteeism in social activities , it perceived that it could create a social order. The implications of a tool of absence its covering a various aspects of the community life. It cause sanctions of shame , fear and also faith in the ancestors , even the establishment of awig - awig is an implied goal that achieved through out the tool itself.